Messages of Da'wah in the Film “Ajari Aku Islam” - Muhammad - Subarkah (Universitas Pendidikan Indonesia, 2021)
Da'wah activities have also grown rapidly in the world of film, including the Film Ajari Aku Islam which looks at the attitudes and actions that non-Muslim men and Muslim women must take when they fall in love. In this film, there are many lessons about young people who never give up on learning Islam. Although, it begins with falling in love with his human being and then in love with his religion. Currently, this phenomenon often occurs today, how the journey of love between different religions makes them blocked by blessing. Then, they chose to change their religion which made their lives further away from their previous religion. Based on this phenomenon, further studies are needed regarding this problem by examining the da'wah messages contained in the film Ajari Aku Islam. The process of understanding the message of da'wah uses the semiotic analysis of Charles Sanders Pierce. The purpose of this study was to determine the message of da'wah in the film Ajari Aku Islam based on Charles Sanders Peirce's analysis. Based on the object, namely the icon, index, symbol. The type of research used is qualitative with descriptive method. The results of this study indicate that the film Ajari Aku Islam which has a duration of 93 minutes contains da'wah messages, namely about religion, morality, help, forbidden to come into contact with non-mahrams, iqra as a tool for learning the Koran, advice and converts. Thus, this film can also be an example for those who are in love with different religions.